Kajian Analisa Usaha Sale Pisang Gulung di UD. Putra Roti Banjarnegara - Magfira Shifa Amartasya; Dwi Ari Cahyani (Proceedings Series on Physical & Formal Sciences, 2021)
Banana sale is an alternative food that is processed by drying. Traditionally, sale processing is done by drying, but some are smoked first with firewood, but this smoking makes the quality of banana sale less good. The business analysis study in this study was to determine the extent to which the banana roll business was profitable, to determine the profit and loss and sustainability of the business managed by UD Putra Roti Banjarnegara. This research was conducted at UD Putra Roti. The location was chosen because UD Putra Roti is one of the most popular food businesses in Banjarnegara district. The research was conducted in October – December 2020. The data collected in the study were primary data and secondary data. The data collected was then analyzed using data analysis. Data analysis methods used, namely: gross income, net income, depreciation of equipment, BEP, RC Ratio, BC Ratio and ROI. Processing of sale banana rolls at UD Putra Roti includes procurement of raw materials, sorting, slicing, arranging, drying, rolling dried bananas, cutting rolls, standing, making dough rolls, frying, draining, and packaging. The results of the analysis show that the sale of banana rolls processing business carried out at UD. Putra Roti is feasible to do with an RC ratio > 1, which is 1.39. BC Ratio of 0.39 and 39% ROI The ROI obtained is 39%, which means that each capital is Rp. 100, obtained a profit of Rp. 39.